2020
DOI: 10.1016/j.ijgfs.2020.100226
|View full text |Cite
|
Sign up to set email alerts
|

Consumer behavior in confinement times: Food choice and cooking attitudes in Spain

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
122
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(167 citation statements)
references
References 8 publications
8
122
0
20
Order By: Relevance
“…In detail, 8% of the Indians and 13% [ 14 ] and 36.8% [ 22 ] of the Italians reduced their daily intake by 25–50%. Similarly, the two Spanish surveys reported a 57.3% decrease in the weekly frequency of consumption in the longitudinal observation by Rodríguez-Pérez et al [ 18 ], and a 27% decrease in the cross-sectional evaluation carried out by Romeo-Arroyo et al [ 15 ].…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…In detail, 8% of the Indians and 13% [ 14 ] and 36.8% [ 22 ] of the Italians reduced their daily intake by 25–50%. Similarly, the two Spanish surveys reported a 57.3% decrease in the weekly frequency of consumption in the longitudinal observation by Rodríguez-Pérez et al [ 18 ], and a 27% decrease in the cross-sectional evaluation carried out by Romeo-Arroyo et al [ 15 ].…”
Section: Resultsmentioning
confidence: 75%
“…In this regard, the only longitudinal observation, carried out by Ghosh et al on a fairly small Indian sample, revealed a 21% increase in the daily consumption of grains and rice [ 13 ]. Similarly, seven cross-sectional observations showed that a large majority consumed higher amounts of cereals [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In particular, homemade pizza, fresh bread, pasta, and rice were found to rule the trend among the Italian and Spanish surveys performed over a wide range of ages and sample sizes (increases by up to 40% and 39%, respectively) [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They started an aggressive publicity action focused on the consumption of this appreciated lamb at cheaper prices; including cost free home delivery [24]. Moreover, such promotions could be of benefit if we consider that baking is a very popular eating habit in Spain [25]. As a result, sales remained stable.…”
Section: Discussionmentioning
confidence: 99%